2019
DOI: 10.7710/1185
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional Collaboration and Patient Health Outcomes in Urban Disadvantaged Settings: A Grounded Theory Study

Abstract: INTRODUCTION Interprofessional interventions improve the ability of health professionals to work in teams, communicate effectively, respect and appreciate each other, and develop shared patient-centric values. While these interventions can change attitudes and beliefs about interprofessional collaboration, the relationship between interprofessional collaboration and patient health outcomes remains poorly understood, particularly for socioeconomically disadvantaged populations. This study sought to explore the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…The IOM's 2001 report concluded that when health care teams communicated well and understood each other's roles, patient care was enhanced. Interprofessionalism can improve teams, increase social capital and trust, and positively impact patient health outcomes (Herbert, 2005;Jadotte et al, 2019;WHO, 2010) The IOM (2013), NASEM (2019), and WHO (2010) all advocate for creating "collaborative ready" graduates capable of joining and promoting team-based models of health care delivery. Systematic reviews conducted between 2007 and 2019 (Guraya & Barr, 2018;Hammick, 2017;Marcussen et al, 2019;Reeves et al, 2016;Reeves et al, 2013;Riskiyana et al, 2018) found 97 studies evaluating the effectiveness of IPE on professional practice and health care outcomes.…”
mentioning
confidence: 99%
“…The IOM's 2001 report concluded that when health care teams communicated well and understood each other's roles, patient care was enhanced. Interprofessionalism can improve teams, increase social capital and trust, and positively impact patient health outcomes (Herbert, 2005;Jadotte et al, 2019;WHO, 2010) The IOM (2013), NASEM (2019), and WHO (2010) all advocate for creating "collaborative ready" graduates capable of joining and promoting team-based models of health care delivery. Systematic reviews conducted between 2007 and 2019 (Guraya & Barr, 2018;Hammick, 2017;Marcussen et al, 2019;Reeves et al, 2016;Reeves et al, 2013;Riskiyana et al, 2018) found 97 studies evaluating the effectiveness of IPE on professional practice and health care outcomes.…”
mentioning
confidence: 99%